Biallelic germline BRCA1 mutations in a patient with early onset breast cancer, mild Fanconi anemia‐like phenotype, and no chromosome fragility. Issue 9 (25th July 2019) - Keupp, Katharina; Hampp, Stephanie; Hübbel, Annette; Maringa, Monika; Kostezka, Sarah; Rhiem, Kerstin; Waha, Anke; Wappenschmidt, Barbara; Pujol, Roser; Surrallés, Jordi; Schmutzler, Rita K.; Wiesmüller, Lisa; et al.
Abstract: Background: Biallelic BRCA1 mutations are regarded either embryonically lethal or to cause Fanconi anemia (FA), a genomic instability syndrome characterized by bone marrow failure, developmental abnormalities, and cancer predisposition. We report biallelic BRCA1 mutations c.181T > G (p.Cys61Gly) and c.5096G > A (p.Arg1699Gln) in a woman with breast cancer diagnosed at the age of 30 years. The common European founder mutation p.Cys61Gly confers high cancer risk, whereas the deleterious p.Arg1699Gln is hypomorphic and was suggested to confer intermediate cancer risk. Methods and Results: Aside from significant toxicity from chemotherapy, the patient showed mild FA‐like features (e.g., short stature, microcephaly, skin hyperpigmentation). Chromosome fragility, a hallmark of FA patient cells, was not present in patient‐derived peripheral blood lymphocytes. We demonstrated that the p.Arg1699Gln mutation impairs DNA double‐strand break repair, elevates RAD51 foci levels at baseline, and compromises BRCA1 protein function in protecting from replication stress. Although the p.Arg1699Gln mutation compromises BRCA1 function, the residual activity of the p.Arg1699Gln allele likely prevents from chromosome fragility and a more severe FA phenotype. Conclusion: Our data expand the clinical spectrum associated with biallelic BRCA1 mutations, ranging from embryonic lethality to a mild FA‐like phenotype and no chromosome fragility. Abstract : Biallelic BRCA1 mutations are regarded either embryonically lethal or to cause Fanconi anemia (FA). We report biallelic BRCA1 mutations, p.Cys61Gly and p.Arg1699Gln, in a woman with early onset breast cancer, comparatively mild FA‐like features, and no chromosome fragility, a hallmark of FA patient cells. The common European founder mutation p.Cys61Gly confers high cancer risk, whereas the deleterious p.Arg1699Gln was suggested hypomorphic. Although the p.Arg1699Gln mutation compromises BRCA1 function, the residual activity of the p.Arg1699Gln allele likely prevents from chromosome fragility and a more severe FA phenotype. Thus, our data expand the clinical spectrum associated with biallelic BRCA1 mutations, ranging from embryonic lethality to a mild FA‐like phenotype and no chromosome fragility.